2003
DOI: 10.1001/jama.290.4.486
|View full text |Cite
|
Sign up to set email alerts
|

Acarbose Treatment and the Risk of Cardiovascular Disease and Hypertension in Patients With Impaired Glucose Tolerance

Abstract: Context The worldwide explosive increase in type 2 diabetes mellitus and its cardiovascular morbidity are becoming major health concerns. Objective To evaluate the effect of decreasing postprandial hyperglycemia with acarbose, an ␣-glucosidase inhibitor, on the risk of cardiovascular disease and hypertension in patients with impaired glucose tolerance (IGT). Design, Setting, and Participants International, multicenter double-blind, placebocontrolled, randomized trial, undertaken in hospitals in Canada,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
896
5
52

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,530 publications
(970 citation statements)
references
References 48 publications
17
896
5
52
Order By: Relevance
“…In contrast, it confirms most of our objections with regard to the methodology and the results of the STOP-NIDDM Trial [2,3,4,5]. Chiasson et al write: "...for patients with risk of cardiovascular events, the number of patients at risk with acarbose treatment is smaller than the number of patients at risk in the placebo group.…”
supporting
confidence: 52%
See 3 more Smart Citations
“…In contrast, it confirms most of our objections with regard to the methodology and the results of the STOP-NIDDM Trial [2,3,4,5]. Chiasson et al write: "...for patients with risk of cardiovascular events, the number of patients at risk with acarbose treatment is smaller than the number of patients at risk in the placebo group.…”
supporting
confidence: 52%
“…However, withholding this information in the publication of results [3,4] and declaring that there was no conflict of interest [3] is misleading.In conclusion, both the STOP-NIDDM Trial and the meta-analysis of selected studies with acarbose are seriously flawed and no valid conclusions can be drawn from the published data. …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…There are several possible reasons for the poorer prognosis in those with worse glycaemic control. Several studies have shown an association between stringent glycaemic control and a lowered risk of developing cardiovascular disease and death [30][31][32], but this finding has not been consistent. In our study, patients in the poorer glycaemic control group tended to have a higher frequency of cardiovascular death, although without statistical significance, probably owing to the relatively small sample size.…”
Section: Discussionmentioning
confidence: 98%